UJI EFEKTIVITAS ANTIOKSIDAN DARI KOMBINASI EKSTRAK DAUN STEVIA (Stevia rebaudiana (bertoni) bertoni) DAN DAUN TEH HIJAU (Camellia sinensis (L.) Kuntze) DENGAN MENGGUNAKAN METODE DPPH (1,1- Difenil-2-Pikrilhidrazil) - Samosir, Sri Rezeki; Auliafendri, Novycha; Naibaho, Marlina Iva (Universitas Imelda Medan, 2024)
The stevia plant is known to have various benefits in the pharmaceutical field and is used as a health medicine because of its antioxidant, antifungal and non-carcinogenic effects. Green tea is a plant that contains various antioxidant compounds that are beneficial for health. The aim of this research is to determine whether the combination of stevia leaf extract and green tea leaves is effective as an antioxidant. Ethanol extract of stevia leaves and green tea leaves is made by maceration with 96% ethanol solvent, combination extract has blackish green. The ethanol extract of stevia leaves and green tea leaves was screened for phytochemical compounds. Antioxidant effectiveness was tested using the DPPH (1,1 Diphenyl-2-Picrylhydrazyl) method, with varying concentrations of 10 ppm, 20 ppm, 30 ppm, 40 ppm and 50 ppm. Then Antioxidant activity test by DPPH measured using a UV-Vis spectrophotometer. The results of screening for phytochemical compounds show that stevia leaf extract contains alkaloids, saponins, flavonoids and tannins. Meanwhile, the results of screening for phytochemical compounds in green tea leaf extract contain alkaloids, steroids, saponins, flavonoids and tannins. The research results showed that antioxidant levels in the combination of Stevia leaf extract and green tea leaves with concentrations of 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm with a ratio of (1:1) had an IC50 analysis result of 10 ppm of 19.90 mg/L, 20 ppm is 12.90 mg/L, 30 ppm is 9.60 mg/L. 40 ppm is 6.80 mg/L. 50 ppm is 6.60 mg/L where a concentration of 50 ppm is classified as a very strong antioxidant. The antioxidant effect of the combination of stevia leaf extract and green tea leaves is still higher than vitamin C. The combination of stevia leaves xtract and green tea leaves has antioxidant effectiveness.